The influence of theory of planned behavior and entrepreneurship education towards entrepreneurial intention - Sri Palupi Prabandari; Puput Ichwatus Sholihah (Universitas Hayam Wuruk Perbanas, 2014)
This present study tries to raise the issue regarding the factors that influence the entrepreneurial spirit of the students of Graduate School. Regarding the finding on the indirect effect of Theory of Planned Behavior on the entrepreneurship through entrepreneurship education, it can be explained that the indirect influence on two variables is as follows: attitude toward entrepreneurship and perceived behavioral control indicates that by stimulating students’ motivation to join entrepreneurship education as outlined previously, students are expected to have entrepreneurial intentions. In addition, entrepreneurship education should be able to prepare students to become entrepreneurs, provide support facilities to start a business, and lecturers must be able to guide the students to become entrepreneurs.